2020
DOI: 10.1016/j.infbeh.2020.101484
|View full text |Cite
|
Sign up to set email alerts
|

Screen time in 36-month-olds at increased likelihood for ASD and ADHD

Abstract:  36-month-old children with elevated ADHD symptoms had the most screen time. Higher screen time was associated with lower receptive/expressive language scores. Screen time was associated with behavioral phenotype, not family history of ASD/ADHD. Screen time reduction strategies and behavioral management support may benefit families of young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…This finding highlights the influence of the sheer volume of screen media time over and above the other variables studied. This finding also supports previous research indicating a negative association between the amount of screen time and language outcomes (e.g., Chonchaiya & Pruksananonda, 2008;Duch et al, 2013;Dynia et al, 2021;Hill et al, 2020;Supanitayanon et al, 2020;Tomopoulos et al, 2010;van den Heuvel et al, 2019). The influence of screen media use, as a molar activity the children engage in on a daily basis, further supports Bronfenbrenner's views.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding highlights the influence of the sheer volume of screen media time over and above the other variables studied. This finding also supports previous research indicating a negative association between the amount of screen time and language outcomes (e.g., Chonchaiya & Pruksananonda, 2008;Duch et al, 2013;Dynia et al, 2021;Hill et al, 2020;Supanitayanon et al, 2020;Tomopoulos et al, 2010;van den Heuvel et al, 2019). The influence of screen media use, as a molar activity the children engage in on a daily basis, further supports Bronfenbrenner's views.…”
Section: Discussionsupporting
confidence: 89%
“…A small number of studies have found positive associations between the quantity of screen media exposure and language outcomes (e.g., Linebarger & Walker, 2005;Roseberry, Hirsh-Pasek & Golinkoff, 2014). However, the majority of the studies that examined the relation between the quantity of foreground and background screen media exposure and language outcomes in young children point to either negative relations (e.g., Chonchaiya & Pruksananonda, 2008;Duch, Fisher, Ensari, Font, Harrington, Taromino, Yip & Rodriguez, 2013;Dynia et al, 2021;Hill, Gangi, Miller, Rafi & Ozonoff, 2020;Hudon et al, 2013;Madigan, McArthur, Anhorn, Eirich & Christakis, 2020;Supanitayanon et al, 2020;van den Heuvel, Ma, Borkhoff, Koroshegyi, Dai, Parkin, Maguire, Birken & TARGet Kids! Collaboration, 2019) or non-significant relations (e.g., Alloway, Williams, Jones & Cochrane, 2014;Schmidt, Rich, Rifas-Shiman, Oken & Taveras, 2009;Taylor, Monaghan & Westermann, 2018).…”
Section: Quantity Of Screen Media Exposurementioning
confidence: 99%
“…At 36-months, participants were classified into one of three outcome groups by a licensed psychologist. Consistent with previous work (Hatch et al, 2020;Hill, Gangi, Miller, Rafi, & Ozonoff, 2020), participants were classified into the "ADHD Concerns" outcome group if they (a) received an examinerrated clinical best estimate outcome of "ADHD Concerns," and (b) exhibited ≥4 DSM-5 ADHD symptoms within any one symptom domain (i.e. inattentive or hyperactive-impulsive) or ≥5 DSM-5 symptoms across both symptom domains (i.e.…”
Section: Participantsmentioning
confidence: 99%
“…Furthermore, in most of the 45 studies, screen time was defined as the amount time that children spent on two activities: watching TV and playing video games. Admittedly, since the publication of the 2014 meta-analysis by Nikkelen et al, several studies on preschool age children have emerged and the results are similar (Hill et al, 2020; Wu et al, 2017; Xie et al, 2020). However, these studies have typically focused on wider range of preschool school age range (i.e., between 3 and 6 years).…”
Section: Introductionmentioning
confidence: 99%